2018
DOI: 10.3389/fnana.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

Neural Damage in Experimental Trypanosoma brucei gambiense Infection: The Suprachiasmatic Nucleus

Abstract: Trypanosoma brucei (T. b.) gambiense is the parasite subspecies responsible for most reported cases of human African trypanosomiasis (HAT) or sleeping sickness. This severe infection leads to characteristic disruption of the sleep-wake cycle, recalling attention on the circadian timing system. Most animal models of the disease have been hitherto based on infection of laboratory rodents with the T. b. brucei subspecies, which is not infectious to humans. In these animal models, functional, rather than structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Double immunofluorescence showed in M. natalensis the occurrence of T. b. gambiense and T. b. brucei outside blood vessels within the brain parenchyma, in variable amounts, at both 4 weeks and 8 weeks (Figure 1 ) after infection, as also presented in the companion article (Tesoriero et al, 2018 ). This indicated that in both paradigms the infection was in the encephalitic stage at the sampled time points.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Double immunofluorescence showed in M. natalensis the occurrence of T. b. gambiense and T. b. brucei outside blood vessels within the brain parenchyma, in variable amounts, at both 4 weeks and 8 weeks (Figure 1 ) after infection, as also presented in the companion article (Tesoriero et al, 2018 ). This indicated that in both paradigms the infection was in the encephalitic stage at the sampled time points.…”
Section: Resultssupporting
confidence: 69%
“…All efforts were made to minimize animal number and suffering. The present investigation was based on the same brains of the animals used for the study of the SCN presented in a companion article (Tesoriero et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early infection of CVOs by trypanosomes is of interest in view of pathogenetic mechanisms of neural dysfunction. In HAT, which is also called sleeping sickness, functional disturbances include a fragmented sleep pattern and alterations of sleep architecture, documented also in experimental infections in rats (55), and a disruption of the sleep-wake cycle, which is a major circadian rhythm, leading to diurnal somnolence and nocturnal insomnia (56). Other circadian rhythms are also disrupted in HAT patients (56).…”
Section: Trypanosome Attack To the Cvosmentioning
confidence: 99%
“…The multimammate mouse, Mastomys natalensis, was used as a rodent model susceptible to both the human parasite T. brucei gambiense and T. brucei brucei, a pathogen not infectious to humans. Interestingly, infection with T. b. gambiense, but not with T. b. brucei, led to a 30% decrease in SCN neuronal density, while astrocyte activation was noted for both (Tesoriero et al, 2018). This, together with the phase shift of melatonin rhythm in human patients (Claustrat et al, 1998), suggests that the effects on host's circadian clocks also exist in human patients.…”
Section: Effects On Circadian Clocksmentioning
confidence: 94%